PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MODEL KOOPERATIF PADA PEMBELAJARAN TEMATIK DI KELAS V SD - Abnas, Arnitsha Van; Marli, Suhardi; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study is to improve the ability of teachers to carry out learning and improve student learning outcomes by applying a cooperative model on thematic learning in class V of Elementary School. The method used is descriptive method, the form of research is classroom action research with research procedures, namely planning, implementation, observation, and reflection. Data collection techniques in the form of direct observation techniques and measurement techniques. Data collection tools in the form of observation sheets and question sheets. The data analysis technique used is the calculation of averages and percentages. The research setting was conducted in the VA class of Pontianak City Elementary School 34. The results of the study are as follows: Increasing the ability of teachers to carry out learning in the first cycle obtained an average of 2.92, Cycle II obtained an average of 3.46 and the third cycle obtained an average of 3.76. Student learning outcomes increase in the first cycle obtained an average of 85.2, the second cycle obtained an average of 86.8 and the third cycle obtained an average of 88.8 all three are high categories. Keywords: Cooperative Learning, Tematik Learning, The Result of Learning.